Service, politics, and engagement: A multi-level analysis - Teimouri, Reza Bahman; Arasli, Huseyin; Kilic, Hasan; Aghaei, Iman (Elsevier, 2018)
This research paper examines a conceptual model that employee engagement has mediating effect on the relationship between service orientation and job embeddedness. In addition, it also examines the perception of organizational politics as a moderator of the relationship between service orientation and job embeddedness. The sample was collected from 47 manager groups from 14 five-star hotels in north Cyprus. The data were analyzed using multi-level analysis following the hierarchical linear modeling of the manner the employees were nested in the departments. The results demonstrated that employee engagement partially mediates the effects of service orientation on job embeddedness. The results also indicated that the relationship between service orientation and job embeddedness was moderated by perceptions of organizational politics, which is an important signal to the hotels in the research context. The paper also identifies possible future directions.
Keywords: Employees; Employee engagement (EE); Job embeddedness (JE); Cyprus; Perceptions of organizational politics (POP); Service orientation (SO)